Comparison of CO2-emissions of households heated by natural gas and firewood - Paládi, Mónika (Acta Geographica Debrecina Landscape & Environment series, 2013)
In terms of climate protection, one of the most important questions is the reduction of the GHG emission. In this study, I compared CO2 -emission of households heated by natural gas and firewood, which had similar heated area and volume of air, considering the carbon-dioxide absorbing of forests of the households heated by firewood. Natural gas is a fossil fuel; however, the firewood (solid biomass) is a renewable energy resource. One of the main features of renewable energy sources is to get into the atmosphere less CO2 than fossil fuels. The renewable energy resources emit into the air just as much CO2 as they absorb during their life cycle.